2015
DOI: 10.1001/jamapediatrics.2014.3291
|View full text |Cite
|
Sign up to set email alerts
|

Central Catheter–Associated Bloodstream Infection Reduction With Ethanol Lock Prophylaxis in Pediatric Intestinal Failure

Abstract: A best-practice CCABSI prevention bundle that included ethanol lock prophylaxis in both the hospital and home was successfully implemented, well tolerated, and demonstrated a significant and sustained reduction in preventable harm in the form of CCABSIs in children with intestinal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 26 publications
2
49
1
Order By: Relevance
“…128,129 Quality improvement studies have previously demonstrated a marked reduction in complication rates associated with CVAD in pediatrics and neonates, indicating that complication rates depend on the care provided by multidisciplinary clinicians. [130][131][132] Previous international focus on the prevention of CVAD complications from organizations such as the World Health Organization and the Centers for Disease Control and Prevention has been solely on CVAD-associated BSI, and generally in the ICU setting.…”
Section: Discussionmentioning
confidence: 99%
“…128,129 Quality improvement studies have previously demonstrated a marked reduction in complication rates associated with CVAD in pediatrics and neonates, indicating that complication rates depend on the care provided by multidisciplinary clinicians. [130][131][132] Previous international focus on the prevention of CVAD complications from organizations such as the World Health Organization and the Centers for Disease Control and Prevention has been solely on CVAD-associated BSI, and generally in the ICU setting.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty two catheters (50.4%) were randomized to group A and fifty one to group B (49.5%). Laboratory parameters on inclusion did not differ either between the two groups ( [27][28][29][30][31][32][33][34][35][36][37][38][39][40] for group B with no statistically significant difference between the two groups. The number of femoral catheter insertion site was small for both groups respectively.…”
Section: Resultsmentioning
confidence: 99%
“…No CRBSI episode was observed during the study period in the ethanol/citrate arm whereas one infective episode was noted in the heparin arm. 27 A randomized blind, placebo-controlled trial, in adult hematology patients with 448 TCCs and 27,745 catheter days, that assessed the efficacy and safety of a daily ethanol lock for the prevention of CRBSI, showed a 3.6-fold, nonsignificant, reduction for patients receiving ethanol (2 of 226 vs. 7 of 222; P 5 0.103). 19 These findings are in keeping with those recorded in a more recent randomized, double blind, multi-center trial of 307 paediatric oncology patients with newly inserted TCCs that were randomly assigned to receive 2 hour ethanol locks (1.5 or 3 mL 70%) or heparin locks (1.5 or 3 mL 100 IU/mL) with a maximum frequency once weekly.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the benefit of antibiotic lock therapy for the prevention of CABSI has not been clarified . Recently, it has been reported that ethanol lock prophylaxis is also effective . Next, we must determine whether these approaches are effective for pediatric patients receiving chemotherapy or stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recently, it has been reported that ethanol lock prophylaxis is also effective. 13,14 Next, we must determine whether these approaches are effective for pediatric patients receiving chemotherapy or stem cell transplantation. Another point of note is that the presence of B. cereus in a blood culture may represent contamination.…”
Section: Discussionmentioning
confidence: 99%